2019
DOI: 10.1111/apa.14779
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study identified fish and milk as the main culprits in cases of food protein‐induced enterocolitis syndrome

Abstract: Aim: Food protein-induced enterocolitis syndrome (FPIES) is a non-immunoglobulin E (IgE)-mediated food allergy, which is confined to the gastrointestinal tract and occurs most frequently in the first year of life. Our aim was to examine the clinical features, causative agents and outcomes of Greek children with FPIES. Methods: This was a five-year (2013-2017) retrospective study, based on chart reviews of 78 children with FPIES from six Greek paediatric allergy centres.Results: Only five children needed an ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 16 publications
(28 reference statements)
8
46
2
2
Order By: Relevance
“…CM, for example, is the most common trigger food in Italy, USA, and Greece, 31,32,33 confirming the results of our population; rice ranks first in Australia 33,34 and is becoming increasingly frequent in the USA. 29 Fish is prevalent in Mediterranean countries, i.e., Italy, Spain, and Gre ece, 31,35,36,37 but in our cohort, it was not as widespread as egg (19%). Similarly to Miceli Sopo S. et al's study, 38 also among our patients with FPIES to fish (n = 11, 13%), the main trigger fish was the sole (n = 8, 73%).…”
Section: Discussionsupporting
confidence: 86%
“…CM, for example, is the most common trigger food in Italy, USA, and Greece, 31,32,33 confirming the results of our population; rice ranks first in Australia 33,34 and is becoming increasingly frequent in the USA. 29 Fish is prevalent in Mediterranean countries, i.e., Italy, Spain, and Gre ece, 31,35,36,37 but in our cohort, it was not as widespread as egg (19%). Similarly to Miceli Sopo S. et al's study, 38 also among our patients with FPIES to fish (n = 11, 13%), the main trigger fish was the sole (n = 8, 73%).…”
Section: Discussionsupporting
confidence: 86%
“…Soya‐induced FPIES is especially frequent in Korea, often associated with CM‐FPIES (up in 43% of patients), but it has a better prognosis and an earlier resolution than in other countries 16 . Fish is one of the most common offending triggers of FPIES in Southern Europe 5,17‐19 and appears to have a poorer prognosis than other foods. Vazquez‐Ortiz et al reported an average age of resolution for fish‐induced FPIES at 60 months, concluding that FPIES to fish resolved over time in most cases, with a 75% cumulative probability of resolution at around 5 years 6 …”
Section: Discussionmentioning
confidence: 99%
“…6 Resolution of FPIES to fish is around 18.8% to 57.0% of cases between 3 to 4.5 years of age. 13,16,22,23 We found a similar rate of 38% tolerance at 4.0 years of age, with an older age of resolution for fish than CM. Due to the low prevalence of multiple FPIES in our cohort, we were unable to compare the age of resolution of single and multiple FPIES.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, the main culprit food was CM, followed by hen's egg, and fish, which differs from the findings in other countries. [7][8][9][10][11][12] The most frequent culprit food was fish in Greece 13 and Spain 10,14 rice in Australia [15][16][17] and the USA, 18 and oats in Taiwan. 19 Soy is frequently reported as a trigger food by North American, British, Australian and Israeli cohorts 4,17,20,21 and was infrequent in our population.…”
Section: Discussionmentioning
confidence: 99%